2018
DOI: 10.1016/j.cmet.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Tracing of Human Clear Cell Renal Cell Carcinomas Demonstrates Suppressed Glucose Oxidation In Vivo

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common form of human kidney cancer. Histological and molecular analyses suggest that ccRCCs have significantly altered metabolism. Recent human studies of lung cancer and intracranial malignancies demonstrated an unexpected preservation of carbohydrate oxidation in the tricarboxylic acid (TCA) cycle. To test the capacity of ccRCC to oxidize substrates in the TCA cycle, we infused C-labeled fuels in ccRCC patients and compared labeling patterns in tumors and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
256
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(276 citation statements)
references
References 35 publications
20
256
0
Order By: Relevance
“…Recent isotope tracing analysis of human ccRCC confirmed enhanced glycolysis and suppressed glucose oxidation by the TCA cycle in these tumors (Courtney et al, 2018), likely due to HIF stabilization caused by frequent von Hippel-Lindau (VHL) mutations (Nickerson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent isotope tracing analysis of human ccRCC confirmed enhanced glycolysis and suppressed glucose oxidation by the TCA cycle in these tumors (Courtney et al, 2018), likely due to HIF stabilization caused by frequent von Hippel-Lindau (VHL) mutations (Nickerson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 For example, we observed higher abundance of glucose and lactate, attributable to the upregulation of glucose transporter 1 35 and lactate dehydrogenase associated with a shift toward aerobic glycolysis. 36,37 Succinate and fumarate, members of the TCA cycle decrease with this metabolism shift, while glutamate increase, coinciding with induction of glutaminolysis. 34 Alterations in glutamine and more generally amino acid metabolism are indeed reflected by the statistical models, which select for N-acetyl aspartic acid, and N-acetyl glutamate peaks in the classification.…”
Section: Discussionmentioning
confidence: 99%
“…PDH plays a crucial regulatory role by tuning glycolytic metabolism in cancer cells . Enhanced glycolysis inhibited pyruvate dehydrogenase flow, and downregulated TCA cycle labeling, consistent with the Warburg effect . Furthermore, several studies reported that SIRT3 expression may be correlated with hexokinase‐1 (HK1) and hexokinase‐2 (HK2) expression in the regulation of glucose metabolism in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%